Relationship of caregivers' schizophrenia literacy and frequency of readmission of their patients with schizophrenia at the national center for mental health: a prospective cohort study - Bajador, Jerico H.; Bermudez, Amiel Nazer C.; Pinlac, Paul Adrian V.; Mira, Nona Rachel C.; Cochin, Kim L.; Antonio, Carl Abelardo T.; Vicente, Bernardino A. (Manila College of Public Health, University of the Philippines Manila, 2020)
Background:
Mental health literacy (MHL) pertain to "knowledge and beliefs about mental disorders which aid their recognition, management and prevention." There were several studies on MHL, but very few when it was applied to a specific mental disorder such as schizophrenia. This study aimed to determine if there is a relationship between caregivers' schizophrenia literacy (SL) and frequency of readmission of their patients with schizophrenia.

Methods:
A prospective cohort study was done to determine the relationship between caregivers' SL and frequency of readmission of their patients with schizophrenia. The first draft of the data collection tool National Center for Mental Health Schizophrenia Literacy-B Questionnaire (NCMHSL-BQ) was pilot tested through structured interview among thirty (30) caregivers from the caregiver-patient pairs in the Admission and Crisis Intervention Section (ACIS) I, II, and III of the National Center for Mental Health. After that, the final NCMHSL-BQ was administered to 380 caregivers from the caregiver-patient pairs who were enrolled from June 2, 2019 to December 2, 2019. Their patients were prospectively followed up after a minimum of six (6) months from discharge to determine whether their patients were readmitted or not; if readmitted, the frequency of dates of readmission were recorded. Log binomial regression and cox proportional hazards regression were performed to analyze data for risk of admission and time of readmission, respectively. Post-estimation statistics were used to assess the goodness of fit of the model. Sensitivity analyses were also conducted for different sets of covariates and data.

Results:
The estimated incidence of readmission of patients with schizophrenia within a six-month follow-up period is 6.4%. A little more than a third of the caregivers had low schizophrenia literacy (SL) at baseline. Relative to patients whose caregivers have high schizophrenia literacy (SL), patients whose caregivers have satisfactory SL have 49% lower risk of readmission (RR=0.51; 95%CI=0.13-1.94, p=0.32), although the association is not statistically significant. In addition, compared to patients whose caregivers have high SL, patients whose caregivers have low SL have 33% lower risk of readmission (RR=0.67; 95%CI=0.20-2.24; p=0.51), although the association is also not statistically significant. As compared to patients whose caregivers have high SL, patients whose caregivers have satisfactory SL and patients whose caregivers have low SL both have longer median time to first readmission, and the survival functions were statistically significantly different (chi square = 6.13, p=0.05). Compared to patients whose caregivers have high schizophrenia literacy (SL), the hazard of readmission of patients whose caregivers have satisfactory SL is 85% lower (HR=0.15, 95% CI: 0.01-2.17, p=0.17), but the association is not significant. On the other hand, patients whose caregivers have low SL have 99.95% lower hazard of readmission (HR=0.0005, 95%CI: 1.93e-06-0.11, p=0.01) than patients whose caregivers have high SL, but the association is highly statistically significant.

Conclusion:
Readmission after six months among patients discharged from first admission at the Admission and Crisis Intervention Section (ACIS) of the National Center for Mental Health was not so common. Though a little more than a third of caregivers have low SL, it does not translate into higher incidence of readmission among their patients. Surprisingly, patients whose caregivers have low SL and patients whose caregivers have satisfactory SL both have relatively lower risk and lower hazards of readmission than those patients whose caregivers have high SL. Caregivers play an indispensable role in keeping and promoting the mental of their patients - keeping them from adverse health outcomes such as readmission.
Includes references and appendices.
Thesis
Keywords: National Center for Mental Health (Philippines); Schizophrenia -- Patients -- Care -- Philippines; Caregivers -- Knowledge, attitudes, practice -- Philippines; Health literacy -- Philippines; Psychiatric hospital patients -- Readmission -- Philippines; Schizophrenia -- Relapse -- Philippines; Mentally ill -- Home care -- Philippines